Strategie preventive dell'infezione da Citomegalovirus nel trapianto di rene - P. Carta; G. Rosso; N. Paudice; A. Larti; M. Zanazzi; L Moscatelli; L. Di Maria; E. Bertoni (AboutScience Srl, 2018)
Abstract non disponibile